2004
DOI: 10.1111/j.1600-0501.2004.01120.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the survival and complication rates of fixed partial dentures (FPDs) after an observation period of at least 5 years

Abstract: This systematic review on cantilever fixed partial dentures indicated that survival and success rates of cantilever fixed partial dentures were lower than those of conventional end-abutment supported FPDs described in a review by Tan et al. (2004) and biological and technical complications were frequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
180
1
13

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(209 citation statements)
references
References 12 publications
9
180
1
13
Order By: Relevance
“…1,2,3 Further improvements toward the successful osseointegration of dental implants have involved modifications to both surface topography and surface chemistry. 4 Implant design (i.e., types and dimensions), surgical procedure, implant placement time, and time prior to loading have been shown to influence implant survival rates.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3 Further improvements toward the successful osseointegration of dental implants have involved modifications to both surface topography and surface chemistry. 4 Implant design (i.e., types and dimensions), surgical procedure, implant placement time, and time prior to loading have been shown to influence implant survival rates.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies on TI-S FDPs reported survival rates of 93.5 % after 40 months [33] and chipping rates of 14.6 % after 24 months [18]. Furthermore, the survival rate for implantsupported FDPs was 95 % after 5 years in service [34]. Furthermore, only few reports exist about the survival rate and the incidence of complications of implant-supported and toothimplant-supported posterior FDPs.…”
Section: Discussionmentioning
confidence: 87%
“…The mechanical complications are common, showing a cumulative incidence of 1.8% in a follow-up done for up to 10 years [18]. Comprehensive analyses of retrieved dental implants are rare in biomechanical and dental literature, as incidences of fractures and failures are considered low.…”
Section: Introductionmentioning
confidence: 99%